Perfectionism, burnout and engagement in youth sport: The mediating role of basic psychological needs. (May 2016) - Jowett, Gareth E.; Hill, Andrew P.; Hall, Howard K.; Curran, Thomas
Abstract: Recent research indicates perfectionistic concerns and perfectionistic strivings share divergent associations with athlete burnout and athlete engagement. Guided by self-determination theory, the present study examined whether these associations were explained by basic psychological needs. Youth athletes (n = 222, M age = 16.01, SD  = 2.68) completed measures of multidimensional perfectionism, athlete burnout, athlete engagement, basic psychological need satisfaction and thwarting. Structural equation modelling revealed that basic psychological need satisfaction and thwarting mediated the perfectionism–engagement and perfectionism–burnout relationships. Perfectionistic concerns shared a negative relationship (via need satisfaction) with athlete engagement and a positive relationship (via need satisfaction and thwarting) with athlete burnout. In contrast, perfectionistic strivings shared a positive relationship (via need satisfaction) with athlete engagement and a negative relationship (via need satisfaction and thwarting) with athlete burnout. The findings highlight the role of basic psychological needs in explaining the differential associations that perfectionistic concerns and strivings share with athlete burnout and engagement. Highlights: Perfectionistic strivings were positively associated with athlete engagement. Perfectionistic concerns were positively associated with athlete burnout. Need satisfaction explained the perfectionism–engagement relationships. Need satisfaction and thwarting explained the perfectionism–burnout relationships.